The Impact of Particulate Matter on the Respiratory System - Yolanda Edith Pratiwi; Feni Fitriani Taufik; Januar Habibi; Adityo Wibowo (Faculty of Medicine Universitas Airlangga, 2023)
Nowadays, around 50% of the world's population lives in cities and urban areas and is exposed to increasingly higher levels of air pollutants including gaseous pollutants and particulate matter (PM). The latter is a key indicator of air pollution transported into the air by a variety of natural processes and human activities. The particles' size has been directly related to their potential impact on health problems. Particles of concern include small particles with diameters of 2.5 to 10 Î¼m (coarse particles) and smaller than 2.5 Î¼m (fine particles). Exposure to air pollutants over a long period of time not only decompensates pre-existing diseases but also leads to pulmonary and respiratory health problems such as asthma, chronic obstructive pulmonary disease (COPD), and lung cancer even in rural areas. A thorough analysis has to be provided to address the implications for policymakers. Hence, more stringent strategies can be implemented to control air pollution and prevent its health effects.